Use of a footrest to reduce low back discomfort development due to prolonged standing - Lee, J.; Baker, R.; Coenen, P.; Straker, Leon (Elsevier, 2018)
© 2017 Elsevier Ltd Prolonged standing is common in many occupations and has been associated with low back discomfort (LBD). No recent studies have investigated a footrest as an intervention to reduce LBD associated with prolonged standing. This study investigated the effect of a footrest on LBD and sought to determine if LBD changes were accompanied by changes in muscle fatigue and low back end-range posture and movement. Twenty participants stood for two 2-h trials, one with and one without a footrest. LBD, lumbar erector spinae electromyography, upper lumbar (UL) and lower lumbar (LL) angles were measured. A significant increase in LBD occurred in both conditions but the footrest did not significantly decrease LBD. The only significant finding between conditions was that UL lordosis became more similar to usual standing over time with footrest use. These findings suggest that footrest use may not reduce LBD development and that development of LBD with prolonged standing is unlikely to be due to muscle fatigue or end-range posture mechanisms.